Behavior of three-chord concrete-filled steel tube built-up columns subjected to eccentric compression - Zheng, Lian-Qiong; Li, Guo-Hong; Zhou, Ji-Zhong; Wang, Zhen-Zhen (Journal of constructional steel research, 2021)
An experimental investigation of a series of three-chord concrete-filled steel tube (CFST) built-up columns was conducted under eccentric compression. The influences of slenderness ratio, eccentricity ratio, eccentricity direction, and brace pattern (battened or laced) on the load bearing process, failure modes, and ultimate load-carrying capacities of the specimens were analyzed. The test results indicate that a CFST built-up column exhibits better performance than a corresponding plain steel built-up column. The ultimate strengths and stiffnesses of the three-chord CFST built-up specimens decreased with increasing slenderness ratio or eccentricity ratio. Battened specimens exhibited lower load-carrying capacities than laced specimens, and different load-bearing capacities were obtained for specimens under different directions of compression eccentricity. Using the proposed equivalent slenderness ratio, three existing design codes were evaluated to predict the stability coefficient, and a new correlation equation considering two failure modes is suggested for calculating the ultimate strength of three-chord CFST built-up columns subject to combined compression and flexure. [Display omitted] •Built-up column slenderness, eccentricity, direction, and brace type are evaluated.•A method to predict the ultimate strength of specimens is proposed.•Equivalent slenderness ratio is adopted to consider influence of shear deformation.•Stability coefficient is determined using GB50936-2014, Eurocode 4, and AISC-1999.•Experimental load capacities are predicted with mean accuracy 0.937 and SD 0.046.